Standard-bearers of equality : America's first abolition movement - Polgar, Paul J. (Omohundro Institute of Early American History and Culture ; University of North Carolina Press, 2019)
"Paul Polgar recovers the racially inclusive vision of America's first abolition movement. In showcasing the activities of the Pennsylvania Abolition Society, the New York Manumission Society, and their African American allies during the post-Revolutionary and early national eras, he unearths this coalition's comprehensive agenda for black freedom and equality"--